The influence of the microbiome on the development and course of bronchial asthma – a comprehensive review - Dacyl, Hubert; Owczarska, Aleksandra; Żerdka, Julia; Brasse, Patryk; Piszka, Mateusz; Kwapień, Eliza; Banach, Jan; Bartkowski, Jakub; Mesyasz, Marceli (Quality in Sport, 2025)
Background Asthma is a chronic airway disease increasingly linked to alterations in the human microbiome. Early-life disruptions in gut, airway, and skin microbiota are associated with impaired immune maturation and higher susceptibility to asthma and allergies. Aim The aim of this study is to review current knowledge on how the human microbiome influences the development, course, and severity of bronchial asthma, including its role in immune regulation, asthma phenotypes, the gut-lung axis, and potential microbiome-based therapies. Materials and Methods This review integrates current evidence using literature from PubMed, Google Scholar, and academic texts with keywords related to the microbiome, gut–lung axis, asthma, dysbiosis, and microbiome-targeted interventions. Experimental, cohort, and clinical studies were analysed. Results The microbiome plays a crucial role in asthma development, especially early in life. Microbial composition is shaped by delivery mode, breastfeeding, antibiotic exposure, and environmental diversity. Cesarean delivery and persistent dysbiosis increase asthma risk, while breastfeeding promotes protective profiles. Early gut dysbiosis - such as reduced SCFA-producing bacteria - affects immune maturation and contributes to distinct asthma phenotypes. Airway colonization by Proteobacteria (e.g., Haemophilus, Moraxella) is associated with severe disease, steroid resistance, and frequent exacerbations. Microbiome-targeted strategies, including probiotics, postbiotics, and fecal microbiota transplantation, show therapeutic potential. Conclusions The microbiome is a key regulator of immune development and a major contributor to asthma risk. Microbiome-based interventions are promising but require further well-designed clinical research.